Alternating 2D and 3D culture reduces cell size and extends the lifespan of placenta-derived mesenchymal stem cells - Pan, Ying; Han, Li; Yang, Yakun; Wu, Xinran; Wang, Aijun; Xie, Liangqi; Zhu, Wuqiang; Wang, Shue; Lei, Yuguo (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundMesenchymal stem cells (MSCs) hold great promise for treating a variety of human diseases; however, their clinical translation is hindered by challenges in large‐scale expansion while preserving therapeutic potency and maintaining small cell size. Conventional 2D culture on rigid substrates induces MSC senescence and enlargement, compromising their function and biodistribution.MethodsWe present an alternating 2D/3D culture strategy that combines adherent monolayer expansion with transient spheroid formation to mitigate these limitations. Placenta‐derived MSCs were cultured under optimized spheroid conditions, with extracellular matrix supplementation and chemically defined media to enhance viability. To address scalability, we developed RGD-functionalized alginate hydrogel tubes (AlgTubes) that enable dynamic transitions between adherent and spheroid states for continuous culture.ResultsSpheroid culture significantly reduced cell size and enhanced immunomodulatory function. The alternating 2D/3D protocol slowed MSC enlargement and senescence over multiple passages while preserving anti-inflammatory activity. Extracellular matrix supplementation and chemically defined media further improved cell viability. AlgTubes successfully supported the alternating culture strategy in a continuous and scalable format.Conclusions The alternating 2D/3D culture system effectively overcomes limitations of conventional MSC expansion by mitigating enlargement, delaying senescence, and preserving both proliferative capacity and immunoregulatory potency. Combined with AlgTube technology, this work demonstrates a promising strategy for MSC manufacturing